HUBUNGAN ANTARA GAYA BELAJAR DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS IV MI CEMOROKANDANG MALANG - Siti Fauziah; lia Nur Atiqoh Bela Dina; Bagus Cahyanto (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
Learning outcomes are influenced by two factors.  namely external factors and internal factors.  One of the internal factors is the way or style of learning , learning style has an important role in achieving maximum learning outcomes .  This study aims to determine the relationship between learning styles and student learning outcomes in science subjects class IV MI Cemorokandang Malang.  This research is a quantitative research using survey research method.  The variables in this study are learning styles (independent variable) and student learning outcomes (dependent variable).  The sample in this study amounted to 50 students.  The data analysis technique in this study used Mann Whitney non-parametric analysis.  which aims to determine whether there is a relationship between learning styles and student learning outcomes in science subjects.  In this research, all calculations use the SPSS_26 program.  Based on the results of the non-parametric analysis of Mann Whitney obtained the value of Sig.  0.001 0.05 means that the hypothesis is accepted.  So it can be concluded that there is a relationship between learning styles and student learning outcomes. Keywords: learning styles, learning outcomes, scince